Study on the perception of gender diversity in secondary school, San Ramón, Costa Rica - Fallas Leitón , Sebastián (2025)
This article had objective is to know the perception students from 8-3 section of the Liceo Experimental Bilingüe de San Ramón have about genre diversity. For this, a study composed by 11 questions about topics like gender diversity, sexual orientation, equity, and sexual diversity was made. A total of 16 of the 24 students participated in the project, and the other 8 did not get the authorization from their parents. We included charts and graphics that summarize the information about the knowledge these students have about the topics studied, where we can observe that the majority of them do have this knowledge. This investigation was made on 2022 as a bachelor honors degree final project.